Coastal Women’s Empowerment: A Legal Study of CSR In Ujong Blang Lhokseumawe, Aceh - Ramziati; Marlia Sastro; Ekogani; Herinawati (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
This study addresses the legal and implementation gap in empowering coastal women through Corporate Social Responsibility (CSR) programs in Indonesia. Despite the mandate under Article 74 of Law Number 40 of 2007 and its derivative local regulation in Aceh (Governor Regulation No. 65 of 2016), which obligates companies to execute CSR initiatives, these programs have failed to effectively strengthen the economic role of women in coastal fishing communities. Focusing on the Ujong Blang beach area in Lhokseumawe, Aceh, this research aims to analyze and propose a viable model for enhancing women's participation in supporting family economics via CSR. Employing an empirical juridical method, the research utilizes primary data from field observations and structured interviews in Ujong Blang, supplemented by secondary data from literature and regulatory reviews. The analysis reveals that existing CSR frameworks lack a targeted mechanism for women's economic empowerment in the studied coastal context. The study concludes that a deliberate partnership model is necessary to create synergy between corporate CSR obligations and the specific socioeconomic needs of coastal women. The findings offer a critical evaluation of current practices and provide a foundational recommendation for designing more effective, inclusive, and legally coherent CSR interventions aimed at strengthening the role of women in coastal family economies. Keywords: Strengthening Roles; Women; CSR; Ujong Blang Beach